Lirika hrvatskih sveučilištaraca - Čović, Marko (Sveučilišni pododbor Matice hrvatske u Zagrebu ;, 1939)
Sadrži stihove M. Andrijaševića, J. Cerinića, Z. Crnkovića, B. Fučića, S. Jakševca, N. Kester-Čaneka, I. Kljaja, V. Korskyja, V. Kosa, D. Malčića, I. Mežnarića, K. Miškarca, F. Niedzielskog, A. Rocca, F. Rubine, I. Sokača, M. Škaričića, D. Štambuka, J. Tursana, S. Vitkovića, M. Vrkljana, M. Vutuca, I. Žunića.